The Ig superfamily protein PTGFRN coordinates survival signaling in glioblastoma multiforme. (10th October 2019) - Aguila, Brittany; Morris, Adina Brett; Spina, Raffaella; Bar, Eli; Schraner, Julie; Vinkler, Robert; Sohn, Jason W.; Welford, Scott M.
Abstract: Glioblastoma multiforme (GBM) is the most malignant primary brain tumor with a median survival of approximately 14 months. Despite aggressive treatment of surgical resection, chemotherapy and radiation therapy, only 3–5% of GBM patients survive more than 3 years. Contributing to this poor therapeutic response, it is believed that GBM contains both intrinsic and acquired mechanisms of resistance, including resistance to radiation therapy. In order to define novel mediators of radiation resistance, we conducted a functional knockdown screen, and identified the immunoglobulin superfamily protein, PTGFRN. In GBM, PTGFRN is found to be overexpressed and to correlate with poor survival. Reducing PTGFRN expression radiosensitizes GBM cells and potently decreases the rate of cell proliferation and tumor growth. Further, PTGFRN inhibition results in significant reduction of PI3K p110β and phosphorylated AKT, due to instability of p110β. Additionally, PTGFRN inhibition decreases nuclear p110β leading to decreased DNA damage sensing and DNA damage repair. Therefore overexpression of PTGFRN in glioblastoma promotes AKT-driven survival signaling and tumor growth, as well as increased DNA repair signaling. These findings suggest PTGFRN is a potential signaling hub for aggressiveness in GBM. Highlights: PTGFRN is widely overexpressed in glioblastoma and dictates poor survival. PTGFRN depletion decreased tumor growth and radiosensitized GBM cells. PTGFRN acts as a scaffolding protein to regulate p110β stability and signaling. Inhibition of PTGFRN depletes nuclear p110β causing decreased DNA damage sensing.